Precision study of the η→μ+μ−γ and ω→μ+μ−π0 electromagnetic transition form-factors and of the ρ→μ+μ− line shape in NA60 - Arnaldi, Roberta; Banicz, Karoly; Specht, Hans Joachim (Physics letters, 2016)
The NA60 experiment studied low-mass muon pair production in proton-nucleus (p-A) collisions using a 400 GeV proton beam at the CERN SPS. The low-mass dimuon spectrum is well described by the superposition of the two-body and Dalitz decays of the light neutral mesons η, ρ, ω, η′ and ϕ, and no evidence of in-medium effects is found. A new high-precision measurement of the electromagnetic transition form factors of the η and ω was performed, profiting from a 10 times larger data sample than the peripheral In-In sample previously collected by NA60. Using the pole-parameterisation |F(M)|2=(1−M2/Λ2)−2 we find Λη−2=1.934±0.067 (stat.) ±0.050 (syst.) (GeV/c2)−2 and Λω−2=2.223±0.026 (stat.) ±0.037 (syst.) (GeV/c2)−2. An improved value of the branching ratio of the Dalitz decay ω→μ+μ−π0 is also obtained, with BR(ω→μ+μ−π0)=[1.41±0.09 (stat.)±0.15 (syst.)]×10−4. Further results refer to the ρ line shape and a new limit on ρ/ω interference in hadron interactions.